PROSPERO at one year: an evaluation of its utility - Booth, Alison; Clarke, Mike; Dooley, Gordon; Ghersi, Davina; Moher, David; Petticrew, Mark; Stewart, Lesley (Université d'Ottawa | University of Ottawa, 2013)
Abstract Background PROSPERO, an international prospective register of systematic review protocols in health and social care, was launched in February 2011. After one year of operation we describe access and use, explore user experience and identify areas for future improvement. Methods We collated administrative data and web statistics and conducted an online survey of users’ experiences. Results On 21 February 2012, there were 1,076 registered users and 359 registration records published on PROSPERO. The database usage statistics demonstrate the international interest in PROSPERO with high access around the clock and around the world. Based on 232 responses from PROSPERO users (response rate 22%), almost all respondents found joining and navigation was easy or very easy (99%); turn round time was good or excellent (96%); and supporting materials provided were helpful or very helpful (80%). The registration fields were found by 80% to be relevant to their review; 99% rated their overall experience of registering with PROSPERO as good or excellent. Most respondents (81%) had a written protocol before completing the registration form and 19% did not. The majority, 136 (79%), indicated they completed the registration form in 60 minutes or less. Of those who expressed an opinion, 167 (87%) considered the time taken to be about right. Conclusions The first year of PROSPERO has shown that registration of systematic review protocols is feasible and not overly burdensome for those registering their reviews. The evaluation has demonstrated that, on the whole, survey respondents are satisfied and the system allows registration of protocol details in a straightforward and acceptable way. The findings have prompted some changes to improve user experience and identified some issues for future consideration.